Interviewing children: the science of conversation in forensic contexts - Poole, Debra A. (American Psychological Association, 2016)
The science of interviewing children -- The forensic perspective -- Conversational habits -- Conventional content: early interview phases -- Conventional content: case issues phases -- Case-specific decisions and exploration -- Protocols and interviewer training